Intussusception following rotavirus vaccination in the Valencia Region, Spain - Pérez-Vilar, Silvia (Hum Vaccin Immunother, 2015)
Studies have shown high intussusception rates in Spain. We performed a hospital-based retrospective observational study of the intussusception risk following rotavirus vaccinations among infants in Valencia, a region of Spain with an annual birth cohort of approximately 48,000 children, during 2007–2011, using a self-controlled case series design. We performed medical record review of all cases using Brighton Collaboration´s case definition and assessed the positive predictive value (PPV) of the intussusception diagnosis code. Among 151 hospitalized cases discharged as intussusception, we confirmed 136 as Brighton Collaboration's Levels 1 or 2, resulting in a PPV of 93% (95% CI: 87%–96%). Three confirmed cases occurred within days 1–7 following the first rotavirus vaccination. The incidence rate ratio was 9.0 (95% CI: 0.9–86.5) (crude) and 4.7 (95% CI:0.3–74.1)(age adjusted). In this first study in Europe, the intussusception risk point estimate was comparable to other studies, although results were not statistically significant, maybe due to limited power. The high PPV found will facilitate implementation of a larger study without requiring medical record review. Our finding of very few vaccinated cases despite a thorough 5-year investigation in a country that, according to previous studies, may have a large background rate of intussusception is reassuring and should contribute to deliberations about the need to include rotavirus vaccines in the official Spanish calendars.